2012
DOI: 10.1074/jbc.m112.375733
|View full text |Cite
|
Sign up to set email alerts
|

Design of Bioactive Peptides from Naturally Occurring μ-Conotoxin Structures

Abstract: Background: -Conotoxins possess interesting blocking effects on voltage-gated sodium channels (Na v s). Results: Based on two known -conotoxins, we designed miniaturized peptides that potently and selectively block Na v s, although they do not contain an ␣-helix. Conclusion: Peptidomimetics constitute a valuable tool to develop novel, synthetic Na v blockers. Significance: Our compounds prove to be an ideal starting platform in the search for therapeutics to treat Na v -related diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 53 publications
(82 reference statements)
2
29
0
Order By: Relevance
“…There are several excellent reviews available describing the Na V channel binding sites and their interaction with toxins in detail (Catterall, 2012;Stevens et al, 2012). The amino acid residues that form the neurotoxin receptor site 1 are primarily located in the pore loop which is formed by the membrane dipping part of the connecting loop between S5 and S6 of each domain (Catterall et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…There are several excellent reviews available describing the Na V channel binding sites and their interaction with toxins in detail (Catterall, 2012;Stevens et al, 2012). The amino acid residues that form the neurotoxin receptor site 1 are primarily located in the pore loop which is formed by the membrane dipping part of the connecting loop between S5 and S6 of each domain (Catterall et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…21,2327 It was further supported by the observation that two-disulfide analogues of μ-KIIIA containing just the [C2-C15] and [C4-C16] bridges showed a similar structure and similar activity profile to those of μ-KIIIA itself. 22,28,29 …”
mentioning
confidence: 99%
“…Our study showed no significant differences between the three-disulfide bridged [Ala 7 ]KIIIA and the disulfide-depleted [Ala 1,7,9 ]KIIIA in potencies and residual currents in blocking Na v 1.2 [33], while recently described disulfide-depleted analogues of KIIIA lacking Cys 1 and Cys 9 exhibited a potent block of Na v 1.2 [31]. Interestingly, while KIIIA was previously reported to share the disulfide pattern typical of the µ-conotoxin family (i.e., 1 st Cys to 4 th Cys, 2 nd to 5 th 3 rd to 6 th ) [32, 33], the disulfide connectivity of the synthetic peptide was recently shown as: 1 st to 5 th 2 nd to 4 th 3 rd to 6 th [34, 35].…”
Section: Resultsmentioning
confidence: 63%
“…Promising in this regard is the observation that a W8E replacement in KIIIA produces a 200-fold decrease in activity against Na v 1.4 [5]. In addition, recent work of Stevens and colleagues [31] showed that chimeric analogues of KIIIA and another µ-conotoxin, BuIIIC, varied in their selectivities for different subtypes of sodium channels. Our work and the recent SAR studies on KIIIA [4, 5, 31] establish the groundwork for next generation KIIIA analogues with improved selectivity profiles and efficacies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation